Psychopathology and urine toxicology in methadone patients. Issue 1 (24th February 2015) - Sadek, Gamal; Cernovsky, Zack; Chiu, Simon
Abstract : Several studies reported high rates of psychiatric commorbidity among methadone patients. We examined the relationships of measures of psychopathology to outcomes of screening urine tests for cocaine, opiates, and benzodiazepines in a sample of 56 methadone patients. They also completed the Symptom Check List-90-Revised (SCL-90-R). The highest scales in the SCL-90-R profile of our patients were those indicating somatic discomfort, anger, phobic anxiety, paranoid ideation, and also obsessive-compulsive disorder symptoms (scores above the 39th per centile). The only significant correlations between urine tests and SCL-90-R psychopathology were those involving benzodiazepines: patients with urine tests positive for benzodiazepines had lower social self-confidence (r=0.48), were more obsessive-compulsive (r=0.44), reported a higher level of anger (r=0.41), of phobic tendencies (r=40), of anxiety (r=0.39), and of paranoid tendencies (r=0.38), and also reported more frequent psychotic symptoms (r=0.43).